Anti-Money Laundering and Combating the Financing of Terrorism : Honduras - World Bank (Washington, DC, 2013)
This Report provides a summary of the level of compliance with the Financial Action Task Force, and provides recommendations to improve compliance within the prevailing context of Honduras. The views expressed in this document are those of the assessment team and do not necessarily reflect the views of the Government of Honduras or the Boards of the World Bank (WB) and International Monetary Fund (IMF). Honduras has set up a number of the fundamental components of an anti-money laundering (AML) regime, through various legislative and regulatory instruments and an institutional framework which includes law enforcement, prosecution, and supervisory bodies. While progress has been made, key changes are needed to laws and regulations in order for Honduras to have more effective money laundering and financing of terrorism regime. There is a lack of strategic direction and coordination among the participants. A focal point and coordination body needs to be established, involving senior representatives of all the entities involved in anti-money laundering and counter-terrorist financing to ensure the most effective and efficient collaboration of the initiative, and to ensure that necessary policy, regulatory and legislative measures can be expeditiously developed, approved and implemented and that initiative wide statistics on workload, performance and results are collected and shared.